2018
DOI: 10.1101/342220
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of psychiatric history and age on self-regulation of the default mode network

Abstract: Real-time neurofeedback enables human subjects to learn to regulate their brain activity, effecting behavioral changes and improvements of psychiatric symptomatology. Neurofeedback up-regulation and downregulation have been assumed to share common neural correlates. Neuropsychiatric pathology and aging incur suboptimal functioning of the default mode network. Despite the exponential increase in real-time neuroimaging studies, the effects of aging, pathology and the direction of regulation on neurofeedback perf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 59 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Small sample sizes are one of the primary reasons for underpowered studies ( Algermissen and Mehler, 2018 ) and yet only three studies ( Jaeckle et al, 2019 , Mehler et al, 2018 , Skouras and Scharnowski, 2019 ) justified their sample size with power calculation (see Table 2 ). Although two studies ( Papoutsi et al, 2018a , Subramanian et al, 2016 ) estimated the number of participants for future studies based on their early-phase results, this procedure can be problematic because it can lead to exaggerated estimates of effect sizes and thus underpowered efficacy studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Small sample sizes are one of the primary reasons for underpowered studies ( Algermissen and Mehler, 2018 ) and yet only three studies ( Jaeckle et al, 2019 , Mehler et al, 2018 , Skouras and Scharnowski, 2019 ) justified their sample size with power calculation (see Table 2 ). Although two studies ( Papoutsi et al, 2018a , Subramanian et al, 2016 ) estimated the number of participants for future studies based on their early-phase results, this procedure can be problematic because it can lead to exaggerated estimates of effect sizes and thus underpowered efficacy studies.…”
Section: Resultsmentioning
confidence: 99%
“…In publications with multiple control groups, an average control group size was calculated first. The two studies using a large dataset from a repository ( McDonald et al, 2017 , Skouras and Scharnowski, 2019 ) were excluded from the count as outliers. Finally, if no control group was included in the study, the study was omitted from the control group count in order to provide a realistic average control group size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others used much wider age ranges of participants ( Hanlon et al, 2013 , Li et al, 2013 ), with some studies including participants ages 18–50 years old ( Hamilton et al, 2011 ) and 18 to 60 years old ( Canterberry et al, 2013 , Hartwell et al, 2016 , Karch et al, 2015 ). Other work beyond the focus of our review has indeed identified age differences in neurofeedback performance, such as a negative correlation between age and default mode network neurofeedback performance in a non-pathological sample of adults aged 20–45 years old ( Skouras & Scharnowski, 2019 ).…”
Section: Future Directions For Real-time Fmri Neurofeedback Researchmentioning
confidence: 99%